TRUST Technique for Neurointervention: A Promising Alternative for Complex Cases - Jiang, Xinzhao; Wang, Peng; Liu, Fang; Wu, Huadong; Jiang, Peng; Yuan, Ruozhen; Zhang, Sheng; Shi, Zongjie (Current Neurovascular Research, 2024)
Background: Neurointervention via Transradial Access (TRA) is becoming increasingly popular as experience with this technique increases. However, approximately 8.6–10.3% of complex TRA cases are converted to femoral access due to a lack of support or radial artery spasm. This study aimed to assess the efficacy and safety of the TRUST (trans-radial coaxial catheter technique using a short sheath, Simmons catheter, and Tethys intermediate catheter) technique in interventional procedures via TRA. Methods: This was a single-center retrospective analysis of 16 patients admitted to our institute between January 2023 to May 2023 to undergo endovascular interventions with the TRUST technique via the TRA. Results: The mean age of the study population was 63.8 years, and 62.5% were male (10/16). The most common procedure was intracranial atherosclerotic stenosis (93.75%, 15/16). All procedures were performed successfully, and the most common procedures in our cohort were ballooning (50.0%, 8/16), stenting (18.75%, 3/16), and both procedures combined (31.25%, 1/16). All procedures were performed using the TRA, and the distal and proximal radial arteries were used for access in 31.35% (5/16) and 68.75% (11/16) of the cases, respectively. Technical success was achieved in all patients and most cases demonstrated mTICI ≥2b recanalization (93.75%, 15/16). In this case, no major access-site complications occurred. Conclusion: The TRUST technique is technically safe and feasible and had a high technical success rate and low complication rate in our study. These results demonstrate that the TRUST technique is a promising alternative for patients undergoing complex neurointerventions.
Keywords: neurointervention